2011
DOI: 10.3109/15569527.2011.554483
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of propranolol in the treatment of parotid hemangioma

Abstract: A 2-month-old female patient presented an extensive bilateral parotid hemangioma (PH) focally ulcerated. Additionally, hepatic ultrasonography revealed a hemangioendothelioma located at right lobe. She was treated with oral prednisolone (3 mg/kg/day) during 10 months with clinical improvement of PH, despite failure to thrive and arterial hypertension. However, regrowth of the lesion occurred after discontinuation of oral steroid. Propranolol hydrochloride (2 mg/kg/day divided into two doses) was then started a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Infantile hemangiomas with deep lesions and segmental morphological characteristics are more prone to prolonged growth. Morais et al indicated that parotid hemangiomas frequently proliferate after 1 year of age and require long‐term treatment. Most Chinese families have only 1 child as a result of family planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infantile hemangiomas with deep lesions and segmental morphological characteristics are more prone to prolonged growth. Morais et al indicated that parotid hemangiomas frequently proliferate after 1 year of age and require long‐term treatment. Most Chinese families have only 1 child as a result of family planning.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of the efficacy and safety of propranolol for the treatment of infantile hemangioma. However, there are few specific articles concerning propranolol treatment for parotid hemangioma, and the total number of such patients is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the efficacy of propranolol and other beta blockers may extend to aggressive vascular tumors. Several reports indicate positive results from beta blockade in patients with moderately threatening vascular tumors including kaposiform hemangioendothelioma, tufted angiomas, parotid hemangioma, Kasabach-Merritt phenomenon, and drug resistant hepatic hemangiomas [16], [17], [18], [19], [20]. It remains to be determined if more malignant vascular tumors such as the rare and understudied metastatic hemangioendotheliomas and angiosarcomas are susceptible to the effects of beta blockade.…”
Section: Introductionmentioning
confidence: 99%
“…The other speculated mechanism by which propranolol works is through vasoconstriction, basic fibroblast growth factor, and matrix metalloproteinases 2 and 9, and in the long term, propranolol may induce apoptosis in the proliferating endothelial cells. 5,6 All four of the present patients were admitted to hospital with a history of stridor and had their diagnosis confirmed on Storz endoscopy. After propranolol treatment, the condition in all patients was relieved within 2 days.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, the mechanism of action of propranolol on IH is thought to be related to a decreased expression of VEGF. The other speculated mechanism by which propranolol works is through vasoconstriction, basic fibroblast growth factor, and matrix metalloproteinases 2 and 9, and in the long term, propranolol may induce apoptosis in the proliferating endothelial cells …”
Section: Discussionmentioning
confidence: 99%